Pattern of Injuries in Homicidal Deaths (Indian Internet Journal of Forensic Medicine and Toxicology, 2010)
The aggressive nature, creative ability and insatiable desire of human to conquer the environment exposes him to severe trauma and violent deaths. One of the components of violent death world wide is homicidal death. Killing of an individual is the highest level of aggression found in all the cultures. Various means used by the assailants are Asphyxiation, Poisoning and Injuries. Injuries in homicidal death cannot be determined on the basis of any general rules; every case has to be considered on its own merit in relation to the particular circumstances obtained at the time of injury. Hence the present prospective study of 2 years duration from October 2005 to Septem ber 2007 was taken up to analyze age distribution of victims, the pattern of injuries, and period of survival in these cases. Homicidal deaths constituted 3.8 % of autopsies conducted. 58 % of homicides occurred in the age group 20-29 years. Sharp weapon injuries were more common (51 %). Defence injuries were common in deaths due to sharp weapon injuries (62 %).
Keywords: Pattern; Injuries; Homicidal deaths.